Pengaruh Penggunaan Sistem Informasi Akuntansi, Tingkat Pendidikan, Gender, Terhadap Keberhasilan UKM Di Kecamatan Buleleng - Suta, Darma Arya; Prayudi, Made Aristia (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of the use of accounting information systems, education level, and gender on the success of SMEs in Buleleng Sub-District. This research method used on this study is a survey research method through a quantitavie approach. The population in this study are SME owners who registered using Micro Credit Program in Buleleng Sub-Distrct. So that the number of samples obtained 146 respondents by determining the purposive sampling technique. The data that has been collected using a questionnaire will be analyzed using a simple linear analysis method and hypothesis testing through SPSS v.24 for Windows program. The results showed that (1) the use of accounting informastion system had a positive effect on the success of SMEs, (2) the level of education had a positive efect on the success of SMEs, and (3) Gender had a positive effect on the success of SMEs in Buleleng Sub-District.